EFEKTIVITAS PERASAN LEMON, MADU DAN CHIA SEED TERHADAP KONSTIPASI PADA IBU HAMIL TRIMESTER III DI TPMB N KABUPATEN BANDUNG - Nova Fitriani, Siska; Septiani Rahayu, Ericha (Journal of Midwifery Tiara Bunda, 2025)
Background: Constipation is a common complaint among pregnant women in their third trimester due to hormonal changes, uterine pressure, and decreased physical activity. The use of natural therapies such as lemon juice, honey, and chia seeds is believed to help improve intestinal peristalsis and defecation patterns. Objective: To determine the effectiveness of a combination of lemon juice, honey, and chia seeds on constipation in pregnant women in their third trimester. Methods: A quasi-experimental study with a pretest-posttest control group design was conducted on 40 pregnant women in their third trimester who experienced constipation at the N District Maternity Hospital in Bandung in 2025. The sample was divided into an intervention group (n=20) that received a combination of lemon-honey-chia seeds 250 ml/day for 7 days, and a control group (n=20) that received education on a high-fiber diet. The level of constipation was measured using the Rome IV Diagnostic Criteria and the Bristol Stool Scale. Data analysis was performed using paired and independent t-tests. Results: Before intervention, the mean constipation score was 6.2 (SD=1.1) in the intervention group and 6.1 (SD=1.2) in the control group. After intervention, the score decreased significantly in the intervention group to 3.1 (SD=0.9), while in the control group it increased to 5.4 (SD=1.0). The t-test showed a significant difference between the two groups (p=0.001). Conclusion: The combination of lemon juice, honey, and chia seeds is effective in reducing constipation in pregnant women in the third trimester.